2018
DOI: 10.1148/radiol.2018171678
|View full text |Cite
|
Sign up to set email alerts
|

LI-RADS for MR Imaging Diagnosis of Hepatocellular Carcinoma: Performance of Major and Ancillary Features

Abstract: Purpose To evaluate the performance of major features, ancillary features, and categories of Liver Imaging Reporting and Data System (LI-RADS) version 2014 at magnetic resonance (MR) imaging for the diagnosis of hepatocellular carcinoma (HCC). Materials and Methods This retrospective institutional review board-approved study included patients with liver MR imaging and at least one pathologically proved lesion. Between 2004 and 2016, 102 patients (275 observations including 113 HCCs) met inclusion criteria. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
98
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 107 publications
(104 citation statements)
references
References 31 publications
6
98
0
Order By: Relevance
“…Our findings are in agreement with prior investigations using LI‐RADS 2014, demonstrating rates of HCC for LR5 observations of 72.6–86% and LR4 of 69–75% . 11.4–26.9% of LR3 observations in our study were HCCs, which is in agreement with a prior investigation using only an extracellular agent . In our study, HCCs categorized as LR3 were significantly larger in size than those that were non‐HCCs for two of the readers.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings are in agreement with prior investigations using LI‐RADS 2014, demonstrating rates of HCC for LR5 observations of 72.6–86% and LR4 of 69–75% . 11.4–26.9% of LR3 observations in our study were HCCs, which is in agreement with a prior investigation using only an extracellular agent . In our study, HCCs categorized as LR3 were significantly larger in size than those that were non‐HCCs for two of the readers.…”
Section: Discussionsupporting
confidence: 93%
“…Darnell et al demonstrated lower sensitivity but similar specificity (42% and 98%, respectively) using extracellular agent and LR2014 criteria; however, their study included only observations ≤20 mm that were detected on antecedent screening ultrasound . An additional prior investigation using extracellular agent and LR2014 criteria demonstrated sensitivity and specificity of 50.8% and 95.8%, respectively, which is in line with our results . Although there have been prior diagnostic performance studies evaluating LI‐RADs with either an extracellular agent or gadoxetate disodium, there have been few that have included both agents within the same study design.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The characteristics of the study population and risk factors for HCC are summarized in Supplemental Table 1 (online). For those diagnosed as HCC without pathology, the follow‐up imaging demonstrated substantial growth, associated with APHE, and washout or enhancing capsule . The reference standards for LR‐1, LR‐2, and LR‐3 observations were based on typical imaging findings or the absence of progression to a malignant category (LR‐4, LR‐5, or LR‐TIV) during the follow‐up period …”
Section: Methodsmentioning
confidence: 99%
“…Hypervascularity in the hepatic arterial phase of dynamic CT or MRI is the hallmark finding in the imaging‐based diagnosis of HCC. Generally, the diagnosis of HCC by arterial phase hyperenhancement (APHE) and washout on CT or MRI shows high specificity . However, HCC does not always show APHE, particularly in the early stage of hepatocarcinogenesis .…”
mentioning
confidence: 99%